The Optimal Wheat Futures Hedge at the Euronext Paris from a Farmer's Perspective - Teresa Vollmer; Stephan von Cramon-Taubadel (German Journal of Agricultural Economics (GJAE), 2020)
Futures contracts are extensively used by commercial market participants to hedge commodities against the risk of adverse price fluctuations. But although farmers have faced increased volatility in commodity prices in recent years, only very few of them actively use hedging as a risk management instrument. In this article we analyze the hedging potential of the Euronext milling wheat futures market for German farmers based on the estimation of optimal static as well as optimal dynamic hedge ratios. We find that both hedging approximately one year and half a year before harvesting leads to a reduction in the variance of returns compared with unhedged portfolios. But this risk minimization is achieved at the cost of lower returns on average. In addition we find that margin calls might be one of the reasons why so few farmers hedge since they cause liquidity problems especially in marketing years with unanticipated price shocks.
Keywords: 330